Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/15564886.2012.747459
|View full text |Cite
|
Sign up to set email alerts
|

The Plight of Providing Appropriate Substance Abuse Treatment Services to Offenders: Modeling the Gaps in Service Delivery

Abstract: Using data from the National Criminal Justice Treatment Practices (NCJTP) Survey, estimates of offenders participating in drug treatment services were generated. Existing drug treatment programs have a capacity to serve around 10% of offenders. The majority of available services are alcohol and drug education and group counseling, which are suited for people with low-threshold substance use disorders. Yet a third of the offenders are reported to have a severe disorder (dependency) requiring Substance Abuse Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Previous research has documented that although about two-thirds of state prison inmates with a history of drug use received any type of treatment prior to incarceration (Mumola & Karberg, 2006), only 33 percent of inmates report receiving any type of drug treatment since admission (Steven Belenko, Houser, & Welsh, 2012). In fact, national data suggests that existing treatment programs have the capacity to serve only about 10 percent of offenders (Taxman, Perdoni, & Caudy, 2013). The current study further shows that race/ethnicity is important to consider when examining utilization of prison services.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented that although about two-thirds of state prison inmates with a history of drug use received any type of treatment prior to incarceration (Mumola & Karberg, 2006), only 33 percent of inmates report receiving any type of drug treatment since admission (Steven Belenko, Houser, & Welsh, 2012). In fact, national data suggests that existing treatment programs have the capacity to serve only about 10 percent of offenders (Taxman, Perdoni, & Caudy, 2013). The current study further shows that race/ethnicity is important to consider when examining utilization of prison services.…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse treatment has the potential to produce beneficial outcomes for offenders under correctional supervision (Chandler, Fletcher, & Volkow, 2009; Lurigio, 2000; Taxman, Perdoni, & Caudy, 2013). Much of the evidence supporting the effectiveness of substance abuse treatment for offenders emanates from evaluations of prison-based therapeutic communities with aftercare upon release (Bahr, et al, 2012).…”
Section: Substance Abuse Treatment For Offendersmentioning
confidence: 99%
“…Improved rates of treatment initiation could significantly reduce failures on community supervision, which fuel the use of jail or prison incarceration as responses to continued drug use (Phelps, 2013). Technology-based interventions may be particularly well suited to justice settings where the workforce has limited training in behavioral health (Bonta, Bourgon, Rugge, et al, 2011; Chadwick, Dawolf, & Serin, 2015) and there are relatively few treatment resources available (Taxman, Perdoni, & Caudy, 2013). One study of a prison-based substance abuse computer education program found that inmates had comparable attendance at a computerized intervention and similar gains in coping skills as traditional counseling groups (Chaple, Sacks, McKendrick, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%